Connectability of protein cages. Issue 6 (18th May 2020) - Majsterkiewicz, Karolina; Azuma, Yusuke; Heddle, Jonathan G.
Abstract : Protein cage assembly and morphology can be controlled by altering connections between protein subunits within the cage or connections between assembled cages. Abstract : Regular, hollow proteinaceous nanoparticles are widespread in nature. The well-defined structures as well as diverse functions of naturally existing protein cages have inspired the development of new nanoarchitectures with desired capabilities. In such approaches, a key functionality is "connectability". Engineering of interfaces between cage building blocks to modulate intra-cage connectability leads to protein cages with new morphologies and assembly–disassembly properties. Modification of protein cage surfaces to control inter-cage connectability enables their arrangement into lattice-like nanomaterials. Here, we review the current progress in control of intra- and inter-cage connectability for protein cage-based nanotechnology development.